CHANGING TREND OF PRESENTATION OF ACUTE CORONARY SYNDROME IN PESHAWAR OVER THE LAST SIXTEEN YEARS - Noor, Lubna; Adnan, Yasir; Khan, Sher Bahadar; Rehman, Hafiz ur; Ahmad, Farooq; Hafizullah, Mohammad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Once considered as disease of the affluent and developed countries, coronary artery disease is emerging as epidemic in the developing world in general and South Asia in particular. Objective: To observe the trend of presentation of acute coronary syndrome in the local population over the last 16 years. Material and Methods: Clinical audit from 1995 to 2010 was carried out in which the data was retrieved from the computerised database of the Department of Cardiology, Lady Reading Hospital Peshawar. The period was divided into four quartiles, and the data of each quartile was analyzed for the total number of admissions, the type of ACS, whether ST-elevated MI or non-ST elevated ACS (comprising unstable angina and non-STEMI), age, gender and mortality. Results: The total admissions into the unit in the first quartile (1995-1998) were 23,827, in the second quartile (1999-2002) 29,005, in the third quartile (2003-2006) 33,206 and in the fourth quartile (2007-2010) were 40,110. Total ACS brunt constituted 8340 (35%), 10,384 (35.8%), 12,180 (36.68%) and 14,920 (37.2%) patients respectively. The mean age of patients was 49.70±6.4 years, 48.21±7.2 years, 47.38±7.1 years and 46.81±6.2 years respectively. Women were 2356 (28.25% of the total ACS burden) in the first quartile, increasing to 3554 (34.225%), 4817 (39.55%) and 6281 (42.1%) in the following quartiles. STEMI constituted 45.88% (3826) of the total ACS presentations in the first quartile, 47.24% (4905) in the second, 49.55% (6035) in the third and 49.87% (7440) in the last quartile. The mortality rate, however, remained constant throughout (8.4% to 8.8%). Conclusion: An increasing trend is seen in the burden of CAD in the local population with increasing presentation as STEMI. It is also evident that CAD is occurring at younger ages and more so in the female population. Keywords: Coronary artery disease, myocardial infarction, unstable angina